Frequency of Hepatitis B, Hepatitis C, and HIV in Blood Transfusion Dependent Thalassemia Patients in a Tertiary Care Hospital - Khan, Shah Abdar; Irshad, Mohammad (Biological and Clinical Sciences Research Journal, 2025)
Children with β-thalassemia major require lifelong blood transfusions to manage anemia, which places them at increased risk of acquiring transfusion-transmitted infections (TTIs) such as hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV). Inadequate screening practices and donor selection in developing countries can contribute to this risk, posing significant morbidity and mortality threats. Objective: To investigate the frequency of Hepatitis B, Hepatitis C, and HIV, thalassemia major patients receiving regular blood transfusions in a tertiary care hospital. Methodology: This cross-sectional study was carried out in the Department of Pediatrics at Lady Reading Hospital, Peshawar, from 29 December 2024 to 29 April 2025. This study was conducted on 136 thalassemia patients aged 1–15 years, confirmed via hemoglobin electrophoresis, and receiving regular transfusions, who were enrolled. HBV, HCV, and HIV infections were diagnosed using ELISA for HBsAg, anti-HCV antibodies and anti-HIV antibodies, respectively. Results: Mean age of 8.07 ± 4.29 years. Male patients constituted 79 (58.1%).The study revealed an HCV presence in 35 (25.7%) cases. HIV in 31(22.8%) cases and HBV in 2 (1.5%) cases. Parental consanguinity was reported in 10 (7.4%) cases while 9 9(72.8%) were vaccinated. Conclusion: HCV was more prevalent, followed by HIV and HBV in thalassemia major patients receiving blood transfusion.